Selenium speciation-dependent cancer radiosensitization by induction of G2/M cell cycle arrest and apoptosis - Nie, Shiqing; He, Xin; Sun, Zhiting; Zhang, Yan; Liu, Ting; Chen, Tianfeng; Zhao, Jianfu (Frontiers in Bioengineering and Biotechnology, 2023)
Radiation therapy has long been an effective treatment modality for non-small cell lung cancer (NSCLC), but radiation resistance and side effects have limited its use. In recent years, the superiority shown by trace element selenium in tumor radiotherapy sensitization has received wide attention. However, different forms of selenium compounds exhibit different chemical properties and their mechanisms of action on tumors may be different. Therefore, we compared the effect and mechanism of different valences of selenium to enhance the radiotherapy of NSCLC. In this paper, the antitumor effects of four different forms of selenium compounds combined with X-rays on SPC-A1 cells were investigated, and their inhibitory effects on the proliferation and migration of cancer cells and their mechanisms were examined. The results showed that these four representative selenium compounds all had a certain ability to enhance the ability of radiotherapy to inhibit tumor cell proliferation and migration, and the mechanism might be related to blocking cell cycle in G2/M phase, activating the caspase cascade and reducing intracellular ROS levels to induce tumor cell apoptosis. Among them, -2-valent organic selenium has the most obvious effect, mainly inhibits cell migration, and induces early apoptosis by activating a large number of caspase-3, and block the cell cycle in S phase and G2/M phase. 0-valent selenium nanoparticles mainly block the cell cycle in G2/M phase. +4-valent inorganic selenium exerts its antitumor effects primarily by inhibiting tumor cell migration and inducing early apoptosis of tumor cells. In conclusion, we found that the radiosensitizing effect of selenium on NSCLC was closely related to its selenium form through the study of the sensitizing effect of different kinds of selenium compounds on radiotherapy.